Chondromesenchymal hamartomas in a 24-year-old male mimicking a posterior mediastinal tumor and a 5-month-old boy with postoperative disseminated intravascular coagulation: two case reports - Yue Li; Danyang Zheng; Min Zuo; Yang Li; Huizhong Zhang (BMC, 2020)
Abstract Background Chondromesenchymal hamartoma of the chest wall is a rare, benign disease that usually presents at birth or in early infancy. It typically involves one or more ribs, forming a unilateral or bilateral extrapleural mass. Patients may be asymptomatic or complain of mild respiratory distress depending on tumor size and location. To the best of our knowledge, only two of the approximately 100 cases reported so far are adults. Case presentation We present two cases of chondromesenchymal hamartoma. The first case involved the left fifth rib in a 24-year-old male, in close proximity to the fifth vertebral body in the left posterior mediastinum, mimicking a posterior mediastinal tumor on imaging. The tumor was excised via thoracoscopy and the patient had an uneventful postoperative course. The second case was that of a 5-month-old boy, who had a tumor involving the left fifth and sixth ribs which caused thoracic cage collapse. Following en bloc resection of the tumor and the involved rib segments, the patient was transferred to the intensive care unit for treatment of pulmonary infection and disseminated intravascular coagulation (DIC). He was discharged from the hospital in stable condition 11 days later. On histopathology, the tumor was found to be a chondromesenchymal hamartoma with immature spindle-shaped mesenchymal cells, plate-like hyaline cartilage, areas of woven bone formation, endochondral ossification and calcification, osteoclastic giant cells, and secondary aneurysmal bone cysts. Conclusions Although the presently reported cases have morphological characteristics similar to previously reported ones, they had distinct radiological and clinical characteristics. Patient 1 is only the third report of an adult with chondromesenchymal hamartoma. His case was characterized by its radiological appearance mimicking a posterior mediastinal tumor. Patient 2 represents the first documentation of DIC as a postoperative complication following excision of a chondromesenchymal hamartoma. We present these two cases to provide clinicopathological insights regarding this extremely rare tumor that are relevant to both pathologists and clinicians.